Clinical observation on holographic meridian scraping therapy combined with auricular bloodletting therapy in treating primary hypertension in the elderly (全息经络刮痧联合耳尖放血疗法治疗老年高血压病临床观察) - ZHEN Chao (郑超); LI Ning (李宁); CAO Hongjing (曹红京) (Association of Integrative Nursing, 2021)
Objective To investigate the effect of holographic meridian scraping therapy combined with auricular bloodletting therapy in the treatment of elderly patients with primary hypertension. Methods Totally 60 elderly patients with primary hypertension were randomly divided into the observation group and the control group, with 30 cases in each group. On the basis of drug therapy and routine health education, the control group received auricular bloodletting therapy, while the observation group received holographic meridian scraping therapy combined with auricular bloodletting therapy. The changes in blood pressure and Traditional Chinese Medicine (TCM) syndrome score were observed, and the intervention effect was evaluated by comparing the improvement of blood pressure and clinical symptoms. Results The systolic pressure and diastolic pressure in the observation group dropped more significantly compared with those in the control group after intervention (P＜0. 05). There was a lower TCM syndrome score in the observation group than that in the control group after intervention (P＜0. 05). There was no significant difference in total effective rate between two groups (P＞0. 05). Conclusion The holographic meridian scraping therapy combined with auricular bloodletting therapy is potentially effective to reduce the blood pressure and relief the TCM syndrome in patients with primary hypertension. (目的 观察全息经络刮痧联合耳尖放血疗法治疗老年高血压病的临床疗效。方法 60例老年高血压病患者根据随机数字表法分为对照组和观察组, 各30例。除常规药物治疗和健康指导外, 对照组实施单纯耳尖放血疗法, 观察组给予全息经络刮痧联合耳尖放血疗法干预。比较2组患者血压和中医证候评分, 评价干预效果。结果 干预后, 观察组收缩压和舒张压下降幅度大于对照组, 差异有统计学意义(P＜0. 05); 观察组中医证候积分下降幅度大于对照组, 差异有统计学意义(P＜0. 05); 观察组总有效率高于对照组, 但差异无统计学意义(P＞0. 05)。结论 全息经络刮痧联合耳尖放血疗法能有效降低老年高血压病患者的血压, 改善中医证候。)